Notas sobre a destruicao de vegetacao e prevencao da rebentacao de toica pelo emorego de fitocidas. - SOUSA, A. Esteves (Maputo, 1963)
Notas sobre a destruicao de vegetacao e prevencao da rebentacao de toica pelo emorego de fitocidas.
Keywords: Vegetacao